Electrical conductivity of 24-hour urine is decreased in patients with calcium oxalate urolithiasis - Boonkam, Kamonchat; Madared, Natcha; Somboon, Pakpum; Pimpin, Alongkorn; Boonla, Chanchai (Chulalongkorn Medical Journal, 2024)
Background: Electrical conductivity (EC) of urine depends on the ionic substance-to-water ratio. Calcium oxalate (CaOx) is the most common type of urinary stone, and its formation is driven by decreased urine volume, increased lithogenic substances, and decreased stone inhibitory compounds (specifically citrate). Low urinary citrate excretion (hypocitraturia) is a prominent risk factor in Thai urolithiasis patients. Objective: To measure the urinary EC, urinary calcium, and urine specific gravity in CaOx stone patients compared with non-stone forming (NSF) subjects. Methods: The urinary EC was measured in 24-hour urine samples obtained from 42 CaOx stone patients and 121 NSF subjects. Urinary calcium and urine specific gravity were measured to evaluate whether they were associated with the urinary EC. Results: The urinary EC of CaOx stone patients was significantly lower than the NSF subjects. The urinary EC level was positively correlated with urine specific gravity, but not urinary calcium. At the selected cutoff of 14.3 mS/cm, the sensitivity, specificity, and accuracy of the urinary EC for diagnosing CaOx urolithiasis were 74.0%, 50.0%, and 56.0%, respectively. In CaOx stone group, patients who had low urinary citrate had lower urinary EC than patients who had high urinary citrate. Experimentally, we demonstrated in artificial urine that citrate concentrations actively influenced the EC values. Decreased citrate level directly caused decreased EC value. Conclusion: The EC of 24-hour urine in CaOx stone patients was decreased relative to the NSF individuals. The urinary EC was linearly correlated with urine specific gravity. Low urinary EC observed in CaOx stone patients possibly resulted from a low urinary citrate excretion that was highly prevalent in the stone patients. In addition, gradual decrease in citrate level caused a gradual decrease in EC level.